2016
DOI: 10.1002/mabi.201600246
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis and Application of n‐Alkyl Cyanoacrylate Surgical Adhesives to the Fixation of Meshes for Hernia Repair

Abstract: The article deals with a comparative analysis of the parameters of the polymerization in physiological conditions of three commercially available alkyl cyanoacrylates, n-butyl cyanoacrylate (GLUBRAN 2), n-hexyl cyanoacrylate (IFABOND), and n-octyl cyanoacrylate (EVOBOND), the cell behavior of the corresponding polymers and the application of these adhesives in the fixation of surgical polypropylene meshes for hernia repair in an animal model of rabbits. The results obtained demonstrate that the curing process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The suitability of these tissue adhesives in the fixation of high-density PP prostheses has already been tested by different authors and by our group in previous preclinical studies [ 22 , 28 , 44 46 ], which showed proper fixation and effective biocompatibility. The main problem of the CAs has turned out to be the general increase in the macrophagic response with respect to the sutures.…”
Section: Discussionmentioning
confidence: 99%
“…The suitability of these tissue adhesives in the fixation of high-density PP prostheses has already been tested by different authors and by our group in previous preclinical studies [ 22 , 28 , 44 46 ], which showed proper fixation and effective biocompatibility. The main problem of the CAs has turned out to be the general increase in the macrophagic response with respect to the sutures.…”
Section: Discussionmentioning
confidence: 99%
“…Having such multipurpose advantages, the tissue adhesives have been explored as hemostats, as drug delivery systems for the delivery of bioactive agents, sealants to prevent fluid or gas loss from the body, and as wound dressings [1,2]. Besides this, tissue adhesives have also been employed for fixation of surgical meshes for hernia repair [3], treatment of meniscus tears [4], abdominoplasty [5], plastic surgery [6] and as bone cements [7]. Though there are numerous tissue adhesives commercially available, none of them is completely devoid of shortcomings.…”
Section: Introductionmentioning
confidence: 99%